The Effect of Project-Based Learning Model with a Multimodal Approach on Student Creativity - Windy Zaerani; Gunawan Gunawan; Kosim Kosim (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2026)
This study aims to examine the effect of the project-based learning model with a multimodal approach on students’ creativity. This study used a quasi-experimental method with a nonequivalent control group design. The study was conducted at SMA Negeri 7 Mataram in class XI of the even semester of the 2025/2026 academic year. Sampling used purposive sampling technique, selecting class XI A3 with 30 students as the experimental class and class XI A2 with 29 students as the control class. The research instrument used a creativity test consisting of 4 essay questions covering indicators of fluency, flexibility, elaboration, and originality. Data analysis was performed using the t-polled variance test. The results showed that the project-based learning model with a multimodal approach significantly influenced students’ creativity, as indicated by a tvalue of 4.196 greater than ttable of 2.002 at a 5% significance level. The average posttest score of the experimental class reached 86, higher than the control class at 71. Thus, the project-based learning model with a multimodal approach is effective in improving students’ creativity.